Design of Electric Drive System for Straddle-type Monorail Car with Independent Intellectual Property Rights - LI Wei; CHEN Wen-guang; CHEN Chao-lu; LIU Ke-an (机车电传动)
Basic parameters and performance requirements were briefed for the electric drive system for straddle-type monorail car with independent intellectual property rights. Also the traction/braking characteristics, performance calculation and line simulation, power circuit structure as well as the design ideas and technical characteristics of the control system were expounded. The vehicle and its electric drive system have passed the field type test and running inspection, which is under trial operation in Chongqing metro line 6 with good situation.